An Updated Checklist of Free-living Marine Nematodes from Coastal India - Datta, Ritika; Maity, Pallab; Bhadury, Punyasloke; Rizvi, Anjum N.; Raghunathan, C. (Zootaxa, 2022)
The present study provides an updated species list of free-living marine nematodes reported from coastal India (Coasts and Islands) based on the thorough consultation of literature published from 1956 to 2022. This exercise resulted in a total of 617 valid species belonging to 266 genera, 48 families, 21 superfamilies and 9 orders. Class Chromadorea comprises 487 species represented by 205 genera, while class Enoplea includes 130 species belonging to 61 genera. The most common family was Xyalidae, with 76 species and the least common families having a single species each were represented by Aegialoalaimidae, Rhadinematidae, Aphanolaimidae, Rhabditidae, Pandolaimidae and Rhabdodemaniidae. The checklist provides a robust framework for the distribution and biogeography of free-living marine nematodes from the Indian waters and could be used to relate with marine ecosystems of other countries.